Use of the Mobius Band structure to challenge 2D flat origins in zero-Waste patternmaking for fashion - Li Z; Cumming D; Kane F; Prescott S (Taylor and Francis Group, 2025)
This practice-led research explores the Mobius Band structure’s potential to challenge zero-waste pattern-making approaches that rely on 2D flat surfaces as a starting point. Addressing textile waste requires alternative methods that are mindful of circular design principles and embrace zero-waste pattern approaches. The Mobius Band structure provides a 3D fabric space for design development, offering the potential for multiple forms and wear possibilities that cater to individual wearer needs, while also contributing to innovations in sustainable apparel production. The experimental work presented in this paper focused on optimising the fluidity and multi-dimensional aspects of the Mobius Band using various materials, sizes, and dimensions, resulting in continuously changing surfaces and garment shapes. The outcomes demonstrate the potential of the Mobius Band method to enhance zero-waste pattern cutting by offering a 3D design framework that reduces cutting lines, prevents fabric waste, preserves fabric integrity, and creates versatile garments with an innovative design approach.
Keywords: Mobius band; zero-waste fashion; textile waste; creative fashion pattern- making; sustainability